Dissecting the role of isoprene and stress-related hormones (ABA and ethylene) in Populus nigra exposed to unequal root zone water stress. (1st July 2017) - Marino, Giovanni; Brunetti, Cecilia; Tattini, Massimiliano; Romano, Andrea; Biasioli, Franco; Tognetti, Roberto; Loreto, Francesco; Ferrini, Francesco; Centritto, Mauro
Abstract: Isoprene is synthesized through the 2-C-methylerythritol-5-phosphate (MEP) pathway that also produces abscisic acid (ABA). Increases in foliar free ABA concentration during drought induce stomatal closure and may also alter ethylene biosynthesis. We hypothesized a role of isoprene biosynthesis in protecting plants challenged by increasing water deficit, by influencing ABA production and ethylene evolution. We performed a split-root experiment on Populus nigra L. subjected to three water treatments: well-watered (WW) plants with both root sectors kept at pot capacity, plants with both root compartments allowed to dry for 5 days (DD) and plants with one-half of the roots irrigated to pot capacity, while the other half did not receive water (WD). WD and WW plants were similar in photosynthesis, water relations, foliar ABA concentration and isoprene emission, whereas these parameters were significantly affected in DD plants: leaf isoprene emission increased despite the fact that photosynthesis declined by 85% and the ABA-glucoside/free ABA ratio decreased significantly. Enhanced isoprene biosynthesis in water-stressed poplars may have contributed to sustaining leaf ABA biosynthesis by keeping the MEP pathway active. However, this enhancement in ABA was accompanied by no change in ethylene biosynthesis, likely confirming the antagonistic role between ABA and ethylene. These results may indicate a potential cross-talk among isoprene, ABA and ethylene under drought.